(untitled) (Economic studies journal, 2020)
The aim of this study is to identify that to what extent external auditors and members of audit committees in Libyan listed companies realize the importance of the use of analytical review procedures in predicting the Company’s continuity. By using the questionnaire to collect data, the results of the study indicate that the external auditors and audit committees of Libyan listed companies realize the role of analytical review procedures in assessing the company’s ability to continue. Although there are some simple differences, there is significant agreement about the importance of these procedures. In addition, they give preference to use the financial indicators in predicting the companies’ continuity.